Effects of Yellow Light on Airborne Microbial Composition and on the Transcriptome of Typical Marker Strain in Ward. (18th May 2022) - Zhao, Xuanqi; Wei, Jing; Chen, Wenjie; Xu, Xuan; Zhu, Ruizhe; Tian, Puyuan; Chen, Tingtao
Abstract : Airborne diseases are transmitted by pathogens in the air. The complex microbial environment in wards is usually considered a major cause of nosocomial infection of various diseases which greatly influences the health of patients with chronic diseases, whereas the illuminant of wards impacts on the microbe especially the disease marker strain is seldom studied. In the present study, high-throughput sequencing was used to study the effect of yellow light on airborne microbial composition, and changes of transcriptome of marker strains Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa, which were isolated from wards, were further studied after the irradiation by yellow light. High-throughput sequencing results indicated that yellow light significantly decreased α -diversity. The relative abundance of Firmicutes at the phylum level, and Clostridium sensu strict o 1, Paraclostridium at the genus level were significantly reduced. RNA sequencing results declared that yellow light significantly downregulated the genes associated with flagella, heme transport system and carbohydrate, amino acid metabolism in E. coli, and the genes related to arginine biosynthesis and the biosynthesis of isoleucine, leucine, and valine in S. aureus . Meanwhile, yellow light significantly upregulated the genes relating to porphyrin metabolism in P. aeruginosa . In conclusion, our work reveals the impacts of yellow light on the microbe in wards, pointing out the application value of yellow light in the prevention of infectious diseases in clinical practice.